Effects of dietary iron sources on growth performance, iron status, Fe-containing enzyme activity and gene expression related to iron homeostasis in tissues of weaned pigs - Huang, Ru-Qu; Yang, Xiao-Jie; Xie, Gao-Mao; Li, Jie; Jian, Yun-Hua; Yang, Jing; Zhu, Yong-Wen (Frontiers in Veterinary Science, 2023)
The aim of this study is to evaluate the effects of dietary iron sources on growth performance, iron status and activities of Fe-containing enzymes and gene expression related to iron homeostasis in tissues of weaned pigs. A total of 480 piglets at d 28 (Duroc X Landrace) were allotted to four groups as a factorial arrangement of treatments with 30 pigs/pen (male: female = 1:1) and 4 replicate pens/treatment. The treatments for iron in the diets were: control basal diet (Con); Con + 150 mg Fe/kg as inorganic Fe (iFe); Con + 75 mg Fe/kg as inorganic Fe + 75 mg Fe/kg as organic Fe-peptide complex (iFe+oFe) and Con + 150 mg of Fe/kg as organic Fe-peptide complex (oFe). The feeding trial lasted for 36 days. There were no significant differences in final body weight, ADG, ADFI, and G/F as well as blood hemoglobin and hematocrit contents between piglets fed the control and iron-supplemented groups (P > 0.05). The iron supplemented groups exhibited increased iron content in the liver, kidney and spleen as well as the CAT and SDH activities in liver compared to the control group (P < 0.05), while piglets in oFe group experienced greater Fe accumulation and activities of CAT and SDH in the liver than piglets in the iFe group. Compared with the control group, dietary supplementation of iron increased the NCOA4 mRNA expression and decreased the TfR1 mRNA expression in liver of piglets. The TfR1, NCOA4 and Ferritin mRNA expressions of bone marrow in both iFe and iFe+oFe groups were greater than both in the Con and oFe groups. These results suggest that dietary supplementation of iron does not influence the growth performance and hematological parameters in weaned pigs fed a corn-soybean meal basal diet (75.8 mg/kg) from d 28 to d 70, but increased tissue iron status and activities of Fe-containing enzymes at d 70. The addition of organic Fe-peptide complexes presents greater beneficial effects on enhancing tissue Fe accumulation and Fe-containing enzyme activities, which may be involved in different gene expression patterns related to iron intake and transport in tissues of weaned pigs.